Addressing Social Bias and Enhancing the Validity of Student Self-Assessment with a Performance Evidence-Based Triangulation Model in Islamic Religious Education Learning - Falahain, Muchtar; Munip, Abdul (Journal of Islamic Education and Ethics, 2026)
This study focuses on the challenges to assessment validity caused by social desirability bias (SDB) when using a self-assessment model to measure students' religious character in Islamic Religious Education (PAI) learning. This research aims to identify the main causes of SDB, collect prior literature on strategies to strengthen assessment validity, synthesize it, and formulate a new concept to overcome SDB and strengthen assessment validity. A qualitative approach, using a literature review, is employed in this study to critically analyze and synthesize scientific literature on SDB, self-assessment, triangulation assessment models, and assessment concepts. Three main findings were successfully demonstrated in this research. First, the main trigger for SDB is students' normative views when assessing their own religious character, so they tend to base their assessments on ideal norms rather than actual daily experiences. Second, the current approach still relies on students' self-assessment data or a general triangulation model. In contrast, efforts to verify student claims through a structured system grounded in authentic behavioral evidence remain lacking. Third, to address these issues, this study proposes the concept of Evidence-Based Performance Triangulation (EBPT) which combines three assessment components: student assessment data, documented evidence of student behavior (e.g., records of worship or daily activities), and validation and comparison of these data, or analytical triangulation., the contribution of this study is a conceptual framework for validation by integrating subjective data and performance evidence to expand the practice of assessing students' religious character.